Role of losses in designing electricity distribution networks - Gan, Chin Kim (2013)
The role and economics of future distribution network design are fundamentally changing. One of the key elements of network design that is yet to be fully incorporated in the design guideline is the life-cycle consideration of network losses, particularly on determining the optimal cable rating in distribution system.